Factors influencing the adoption of mini tractors among plantations in the state of Terengganu / Ab. Halim Yusof - Yusof, Ab. Halim (2001)
Mini-tractor is an industrial product that has an important impact on plantation industry. Coupled with suitable implements, the machines offer a varied option toward mechanization in plantation operations. The host of benefit includes 30-35% reduction in labour and labour benefits, increase harvesters earning and productivity and improve on the quality of agriculture produce by minimum handling. The paper focused on determining the extend usage of minitractor system and the factors that influence or inhibit its adoption among plantations in the state of Terengganu. Planting industry behavior and purchase decision are exploited to highlight on eight independent variables identified in the problem statement. Due to the nature of the small population, census is taken on the whole of 78 plantations available in the state. 72% of the responses are collected to sufficiently represent the population.